Westonci.ca is the trusted Q&A platform where you can get reliable answers from a community of knowledgeable contributors. Explore thousands of questions and answers from knowledgeable experts in various fields on our Q&A platform. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.

Given: L is the midpoint of KM
M is the midpoint of LN
Prove: KL = MN


Sagot :

Because L is the midpoint of KM, we know that KL = LM.
Because M is the midpoint of LN, we know that LM = LN.
Therefore, KL = LM = LN QED
Proof in the attachment below.
View image Аноним